2021
DOI: 10.3389/fmicb.2020.622454
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Fertilization on Ammonia-Oxidizing Microorganisms and Nitrification in Brown Soil of Northeast China

Abstract: The objective of this study was to find out changes in ammonia oxidation microorganisms with respect to fertilizer as investigated by real-time polymerase chain reaction and high-throughput sequencing. The treatments included control (CK); chemical fertilizer nitrogen low (N) and high (N2); nitrogen and phosphorus (NP); nitrogen phosphorus and potassium (NPK) and organic manure fertilizer (M); MN; MN2; MNPK. The results showed that long-term fertilization influenced soil fertility and affected the abundance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Whereas other sRNAs (Dsr11, Dsr18, Dsr39, Qpr6, and OsiA) in D. radiodurans have been characterized as important regulators under other stresses (i.e. H 2 O 2 and heat stress) 39 , 40 , 54 – 56 , PprS has been the only sRNA identified to impact survival and growth uniquely post-IR exposure. These results suggest that PprS is unique among known sRNAs in D. radiodurans in its contribution to IR recovery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas other sRNAs (Dsr11, Dsr18, Dsr39, Qpr6, and OsiA) in D. radiodurans have been characterized as important regulators under other stresses (i.e. H 2 O 2 and heat stress) 39 , 40 , 54 – 56 , PprS has been the only sRNA identified to impact survival and growth uniquely post-IR exposure. These results suggest that PprS is unique among known sRNAs in D. radiodurans in its contribution to IR recovery.…”
Section: Resultsmentioning
confidence: 99%
“…To delete sRNA coding regions from the genomes of D. radiodurans , we used a suicide plasmid to introduce the desired interruption by homologous recombination as previously reported 56 . Briefly, the upstream and downstream homologous regions of the sRNA to be deleted were cloned into pUC19mPheS plasmid which contains kanamycin resistance, lox66 and lox71 sequences.…”
Section: Methodsmentioning
confidence: 99%
“…Our global synthesis confirmed this point of view as soil total N drives GHN and is also an important factor controlling GAN. Soils with a higher total N content usually have a higher MB (Elrys et al, 2021) and higher AOB and AOA abundances (Cai et al, 2020), stimulating GN rates. Soil total N increased GN probably by directly providing NH 4 + substrate for soil microbes (Cai et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, mineral fertilization has been found to reduce microbial diversity, including the plant-beneficial microbial taxa [76]. Meta-analysis of microbial communities, based on 107 datasets from 64 long-term trials from around the world, concluded that mineral fertilizer application (in particular N fertilizer treatment) leads to a 15.1% increase in microbial biomass compared to unfertilized control plots; moreover, N application (urea and ammonia fertilizers) can have a temporary or stable effect in increasing pH [77][78][79]. However, the use of a chemical fertilizer alone does not lead to a remarkable increase in soil microbial abundance.…”
Section: Effects Of Chemical Fertilizers On Biomass Activity and Diversity Of Soil Microorganismsmentioning
confidence: 99%
“…In this study, the AOA structure was more negatively affected. The long-term application of chemical NPK or N fertilizer has been found to significantly affect soil microbial communities throughout the soil profile and increase the relative abundance of AOA in surface soil (0-40 cm) only in the presence of additional organic fertilization (recycled crop residues or manure) [79,138]. This implies that the important ecological function of soil nitrification can be promoted only with simultaneous chemical and organic fertilization.…”
Section: Bacterial and Fungal Species Affected By Chemical Or Organic Fertilizersmentioning
confidence: 99%